Shakespeare's scribe - Blackwood, Gary L. (New York : Dutton Children's Books, 2000)
In plague-ridden 1602 England, a fifteen-year-old orphan boy, who has become an apprentice actor, goes on the road with Shakespeare's troupe, and finds out more about his parents along the way.
Sequel to: The Shakespeare stealer.
Keywords: Shakespeare, William, -- 1564-1616 -- Fiction; Theater -- Fiction; Orphans -- Fiction; Actors and actresses -- Fiction; Plague -- England -- Fiction; Great Britain -- History -- Elizabeth, 1558-1603 -- Fiction